Le Canada ou partie de la Nouvelle France dans l'Amerique Septentrionale, contenant la Terre de Labrador, la Nouvelle France, les Isles de Terre Neuve, de Nostre Dame, etc. : á l'usage de Monseigneur le Duc de Bourgogne - Alexis Hubert Jaillot 1632?-1712. (Creator)
French map of New France (Québec), Newfoundland and Labrador. Bodies of water are labelled. English and French posts are labelled. Text next to some of the French posts describe efforts to cut off movement of Indigenous people into the area. Scale is ca. 1:6,000,000. Key in the upper right corner shows the scale in various leagues. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .